Batasan Privasi Dalam Hukum Islam: Analisis Fenomena Oversharing di Media Sosial - Nurhikma; Idris Alfarizi; Kurniati (Jurnal Ilmu Hukum, 2025)
The phenomenon of oversharing on social media has become a significant issue in the digital age, where individuals often over-share personal information without regard to its impact. In the context of Islamic law, privacy is a fundamental value that must be maintained to protect the honor and dignity of individuals. However, research linking privacy principles in Islamic law with privacy challenges in social media is still limited. This research uses a qualitative method with a literature study approach and normative analysis of Qur'anic verses, hadith, and scholars' opinions to examine the limits of privacy in Islamic law and its implications for oversharing practices on social media. The results show that Islamic law regulates privacy through Maqasid al-Shari'ah, the prohibition of tajassus, and the recommendation to maintain speech and behavior in public spaces. The practice of oversharing on social media can violate these principles, potentially leading to slander, data exploitation, and negative impacts on social and psychological relationships. In addition, education about digital ethics based on Islamic law is important to encourage wise and responsible use of social media. This research makes a novel contribution to understanding the relationship between sharia norms and privacy challenges in the technological age, while offering ethical guidance for social media users to maintain honor and safety in the digital world.